Chemical Constituents of Supercritical Extracts from Alpinia officinarum and the Feeding Deterrent Activity against Tribolium castaneum - Xin, Mintong (Molecules, 2017)
Alpinia officinarum has been confirmed to possess bioactivities against some pests. In this work, a sample was obtained from A. officinarum rhizomes by supercritical fluid CO(2) extraction (SFE). According to GC-MS analysis, the main chemical components for SFE-sample included benzylacetone (26.77%), 1,7-diphenyl-5-hydroxy-3-heptanone (17.78%), guaiacylacetone (10.03%) and benzenepropanal (7.42%). The essential oil of A. officinarum rhizomes (LD(50) = 20.71 μg/adult) exhibited more contact toxicity than SFE extract (LD(50) = 82.72 μg/adult) against Tribolium castaneum. From SFE extracts, one new compound, 1-phenyl-4-(16,17-dimethyl-9,13-octadiene)-5-isopentenyl-7-(4”-methoxyl-3”-hydroxyl-phenyl)-3-heptanone (3), together with five known compounds identified as 5-hydroxy-1,7-diphenyl-3-heptanone (1), 1,7-diphenyl-4-hepten-3-one (2), galangin (4), galangin-3-methyl ether (5) and pinocembrin (6), were isolated and their feeding deterrent activities against T. castaneum adults were assessed. It was found that compounds 1–6 had feeding deterrent activities against T. castaneum with feeding deterrent indices of 18.21%, 18.94%, 19.79%, 26.99%, 20.34%, and 35.81%, respectively, at the concentration of 1500 ppm. Hence, the essential oil and SFE extracts/compounds of A. officinarum rhizomes represent promising alternatives in the control of T. castaneum adults.